(untitled) (MAUSAM, 2026)
Understanding precipitation projections under climate change in semi-arid regions such as South Bihar is crucial for water-resources planning. This study examines the impacts of a high-emissions scenario (RCP 8.5) on drought patterns across the southern districts of Bihar using outputs from 14 downscaled, regionally adjusted global climate models (GCMs). Meteorological drought is characterized with the Standardized Precipitation Index (SPI). Model performance was evaluated by correlating GCM precipitation with India Meteorological Department (IMD) observations for 2006–2020; the best-performing models were HadGEM2-AO, MRI-CGCM3, MIROC5, CESM1-CAM5, and CCSM4. Projections indicate an 30% increase in the severity of mild-to-moderate droughts, with Gaya, Jamui, and Lakhisarai most affected. The likelihood of rainless spells during 2021–2050 is projected to rise, signalling a growing risk of dry spell driven meteorological drought. While individual drought events cannot be predicted deterministically, the evolving rainfall regime suggests greater alternation between wet and dry conditions. Strong agreement between simulated and observed precipitation (R² 0.63–0.73) supports the suitability of these models for assessing future drought risk in this region.